Chronotherapy - Clock Of Curing - P. SRINIVAS; G. SANDEEP; A. ROHAN PRIDHVI; Y. SOUJANYA (International Journal of Pharma and Bio Sciences, 2011)
The present review deals with treatment to various disorders with normal body rhythms like Ultradian, Circadian, Infradian & Seasonal. The basics of Chronotherapy and its advantages and disadvantages following the marketed technologies for the drug-chronotherapy are focused. The rational therapy to various diseases like: Hypertension, Bronchial asthma, Peptic ulcers, Myocardial infarction, Arthritis, Cerebrovascular accidents & Hypercholesterolemia by Chronotherapy is also enlightened. The regulatory concern on Chrono-Pharmaceuticals is glanced.